2016
DOI: 10.1080/08927022.2016.1185793
|View full text |Cite
|
Sign up to set email alerts
|

Concentration effect of cimetidine with POPC bilayer: a molecular dynamics simulation study

Abstract: a tianjin Key laboratory of Molecular Design and Drug Discovery, tianjin institute of Pharmaceutical research, tianjin, P.r. china; b State Key laboratory of Drug Delivery technology and Pharmacokinetics, tianjin institute of Pharmaceutical research, tianjin, P.r. china ABSTRACT All-atom molecular dynamics simulations have been performed on cimetidine in the presence of a palmitoyloleoylphosphatidylcholine (POPC) bilayer. The free energy profile of a single cimetidine molecule passing across POPC bilayer displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Our previous work suggested that TNT molecules previously entering the membrane will promote the permeability of the latter molecules in the membrane, and the VDW interactions between TNT molecules play the main role in their attraction and clustering . Wang et al reported that 8 mol % of cimetidine would lead to a decrease in the ability of subsequent cimetidine molecules across the membrane, which was attributed to the insignificant interactions between cimetidine molecules . Therefore, we calculated the VDW energy between the explosive molecules during their membrane adsorption process in a mixture system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous work suggested that TNT molecules previously entering the membrane will promote the permeability of the latter molecules in the membrane, and the VDW interactions between TNT molecules play the main role in their attraction and clustering . Wang et al reported that 8 mol % of cimetidine would lead to a decrease in the ability of subsequent cimetidine molecules across the membrane, which was attributed to the insignificant interactions between cimetidine molecules . Therefore, we calculated the VDW energy between the explosive molecules during their membrane adsorption process in a mixture system.…”
Section: Resultsmentioning
confidence: 99%
“… 22 Wang et al reported that 8 mol % of cimetidine would lead to a decrease in the ability of subsequent cimetidine molecules across the membrane, which was attributed to the insignificant interactions between cimetidine molecules. 49 Therefore, we calculated the VDW energy between the explosive molecules during their membrane adsorption process in a mixture system. It can be seen from Figure 6 that the VDW energy between RDX molecules (VMD-RR) is very weak and quickly decreased to almost zero, even showing repulsion to each other.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in the TNT-40 system, the more pronounced changes in the free energy profile might be related to the formation of the membrane-spanning aggregate, in which some TNT molecules could stably reside in the hydrophobic core, and further affect the local barrier of the bilayer center. In the recent simulation, Wang et al 49 reported the effect of concentration on the adsorption and transmembrane process of cimetidine. In detail, 8 mol% of cimetidine would lead to a decrease in the ability of subsequent cimetidine molecules across the membrane and a decline of passive permeability, which was attributed to the insignificant interactions between cimetidine molecules.…”
Section: Resultsmentioning
confidence: 99%